1964
DOI: 10.1021/jo01028a060
|View full text |Cite
|
Sign up to set email alerts
|

Organic Polysulfides.1 IV. Synthesis of Bis(triphenylmethyl) Polysulfides

Abstract: mole) was heated in a solution of sodium carbonate (10.6 g., 0.01 mole) in 150 ml. of 33%, ethanol until it dissolved. The solution was refluxed for 2 hr. with stirring and, after storage overnight in the cold (0°), sodium carbonate was filtered off and the filtrate was evaporated to dryness under reduced pressure. The solid residue was taken into hot benzene, and the benzene solution was concentrated to a semisolid. Petroleum ether was added, and the precipitate, obtained after storage in the cold (0°) overni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…showed only two obvious maxima at 242 (E = 1.3 x lo4) and 309 mp (E = 2.4 x lo4) while the disulfide had maxima at 294 (E = 2.8 x lo4) and 304 mp (E = 2.9 x lo4). These spectra do not closely resemble those of either typical alkyl polysulfides (32,33) or typical Schiff's bases (34). Judging from the increase in extinction coefficients in the 300 mp region for the Can.…”
Section: Spectra Of Benzylidenimine Polysulfidesmentioning
confidence: 87%
“…showed only two obvious maxima at 242 (E = 1.3 x lo4) and 309 mp (E = 2.4 x lo4) while the disulfide had maxima at 294 (E = 2.8 x lo4) and 304 mp (E = 2.9 x lo4). These spectra do not closely resemble those of either typical alkyl polysulfides (32,33) or typical Schiff's bases (34). Judging from the increase in extinction coefficients in the 300 mp region for the Can.…”
Section: Spectra Of Benzylidenimine Polysulfidesmentioning
confidence: 87%
“…Note that these exchange reactions may serve not only to generate crosslinks but also to alter the rank of bis‐PMN‐allylic polysulfides. A third possible crosslinking mechanism involves the oxidation of hydropersulfides by persulfenyl bromides to generate 4 and HBr 28, 29. The latter would be subsequently scavenged by epoxide.…”
Section: Discussionmentioning
confidence: 99%
“…32 Later, in 1964, Takeshiga Nakabayashi demonstrated that triphenylmethanethiol (TrSH) could be used for both bis(triphenylmethyl)tri-and tetrasulfane synthesis using SCl 2 and S 2 Cl 2 , respectively. 33 Also, in the 1920s, a variety of thiocarbonates were used as non-thiol, sulfur nucleophiles such as potassium thiobenzoate, 34 Bender's salt (EtOCO(SK) = potassium O-ethylthiocarbonate), 35 potassium O-ethyldithiocarbonate (EtOCS(SK)), and potassium ethyl trithiocarbonate (EtSCS(SK)), which gave rise to end-substituted trisulfides. 35 The trend in using non-thiol nucleophiles continued with Franz Fehér's contributions in 1958 36 using mercuric thiocyanate for accessing NC-(S) n -CN polysulfanes, covering both tri (n = 3, from SCl 2 ) and tetra…”
Section: Methodology C: 2 × Rsm + Lg(s) N Lg (N = 1 2)mentioning
confidence: 99%